Making Money Out of Football. (February 2015) - Leach, Stephanie; Szymanski, Stefan
Abstract In the US, most economists argue that professional sports teams are profit‐maximising businesses, but it is a widely held view in Europe that professional football clubs are not run on a profit‐maximising basis. This belief has important implications for the impact of widely‐advocated policy measures, such as revenue sharing. This paper looks at the performance of 16 English football clubs that acquired a stock exchange listing in the mid‐1990s. If the European story is true, we should have observed a shift toward profit‐maximising behaviour at these clubs, under the assumption that investors were attracted to these football clubs to earn a positive return. This paper finds no evidence of any shift in the behaviour of these 16 clubs after flotation. This result is consistent with the view that football clubs in England have been much more oriented toward profit objectives than is normally assumed.